The Canadian pulp and paper industry: An economic and environmental analysis - Azarafshar, Elham (University of Ottawa (Canada), 2005)
This thesis looks at the Canadian Pulp and Paper Industry at both the empirical level and the theoretical level. In the first half of the thesis, the empirical aspects of the industry are studied within the framework of the trade-off between environmental protection and efficiency of the plants. In the second half, several theoretical issues related to the market structure of the pulp and paper industry are analyzed. Chapter 1 provides an overview of the Canadian Pulp and Paper Industry and the various production processes. In Chapter 2, an empirical analysis is undertaken to study the relation between technical efficiency and pollution. This analysis has far-reaching policy implications as it allows us to study empirically the effect of pollution control regulations on the performance of the firms. Chapter 3 contains a study on the international trade in market pulp, with specific focus on the trade among Canada, US, and Europe. A multi-market spatial oligopoly model is formulated, calibrated, then simulated to gain insights into the workings of these interdependent markets. In Chapter 4, an oligopoly model for the tissue and towel market in North America is formalized then calibrated. The objective of this chapter is to obtain an adequate picture of the consumer market, in which prices, qualities, and advertising are used to entice consumers. The model contains four firms, which produce a total number of ten brands among them. The simulation of the model yields detailed results on the intricate workings of the industry and results that cannot be expected from simple text-book oligopoly models.
Keywords: Economics, General.